ANALISIS PENURUNAN KUALITAS MUTU IKAN CAKALANG YANG DISIMPAN PADA SUHU RUANG - Thoy Batun Citra Rahmadani; Laily Fitriani Mulyani; Rangga Idris Affandi (Journal of Fish Nutrition, 2025)
The objective of this research was to determine the decline in freshness of skipjack tuna stored at room temperature. Fish freshness testing was carried out using organoleptic tests such as eyes, gills, odor and texture of the fish, as well as counting the number of bacteria taken from the gills of skipjack tuna. Skipjack tuna was taken from 3 different markets in Mataram City. Observations on the fish were carried out twice, the first in the morning after the fish was taken from the market at 09.00 WITA and the second observation at 15.00 WITA. The results of the study showed that in the morning the skipjack tuna was in a condition of declining quality freshness, then during the day the quality of the skipjack tuna decreased further with a condition that was almost rotten. The results of observations of total bacteria also showed that in the morning the total bacteria had passed the predetermined threshold and during the day the number of bacteria increased until it could not be counted.